Theoretical approaches to the contents and factors of emergence of tax risks at the enterprises of the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
Instability of world economy, characteristic for the present, causes thedominating role of the preventive risk management allowing enterprisestructures purposefully and with anticipation to react to the arising risks,preventing threat of inadmissible decrease in efficiency of business activityunder the influence of risks. In article the main characteristics inherent intax risk are defined functions of tax risk are allocated. Also need of the organizationof scientific researches, uses of various methods of decrease intax risks at the enterprise, development of strategy of management of risk,in the form of forecasting of risks locates. also measures for their account,for the purpose of decrease in tax risks are offered. Conclusions are drawnthat tax risks in the Republic of Kazakhstan are subject to the analysis andan assessment, them it is possible and it is necessary to operate.
Keywords: tax risks; assessment of tax risks; risk management; identification of risks; enterprise risk; accounting risk; emergence of accounting risks; ways of decrease in risk; function of tax risk; size of tax risk.